2021
DOI: 10.1007/s10745-021-00248-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Smallholder Maintenance of Crop Diversity in Morocco’s High Atlas Mountains

Abstract: Smallholder farmers are important managers of global crop diversity. However, agricultural modernization is changing farming practices and raising questions about the socio-ecological factors that support crop diversity. In the context of the semi-arid High Atlas Mountains in Morocco, we explored determinants of crop diversity through a cross-sectional survey and farmer interviews in villages adopting new crops such as apples. Through a multiple linear regression analysis and farmer interviews, we found that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
(70 reference statements)
1
1
0
Order By: Relevance
“…Feintrenie et al (2010), for example, observed in Indonesian agroforestry systems that economic dimension takes precedence over other values, such as cultural or sentimental attachment, and can quickly transform a diversified system into a monoculture. However, our study found that market integration does not necessarily mean lower crop diversity, as documented in previous studies (Goldberg et al, 2021;Vadez et al, 2004).…”
Section: Discussionsupporting
confidence: 81%
“…Feintrenie et al (2010), for example, observed in Indonesian agroforestry systems that economic dimension takes precedence over other values, such as cultural or sentimental attachment, and can quickly transform a diversified system into a monoculture. However, our study found that market integration does not necessarily mean lower crop diversity, as documented in previous studies (Goldberg et al, 2021;Vadez et al, 2004).…”
Section: Discussionsupporting
confidence: 81%
“…This is because although agrobiodiversity can be used to mitigate risks and stabilise both yields and incomes (Kremen and Merenleder, 2018), farmers' short-term decisions are often based on how 'pro table' crop varieties or livestock breeds are (Bellon et al, 2020). Global market integration, land use change and migration further contribute to changing farmer maintenance of crop diversity (Zimmerer and de Haan, 2017; Goldberg et al, 2021).…”
Section: Introductionmentioning
confidence: 99%